PENGARUH POLA SIRKULASI PUSAT PERBELANJAAN MAL TERHADAP POLA PENYEBARAN PENGUNJUNG Studi kasus: Margocity, Depok - Syoufa, Ade; Hapsari, Helen (Universitas Gunadarma, 2014)
This study aimed to determine the relationship of the circulation pattern which is owned by the shopping center on the pattern of spread of visitors. Circulation patterns that are the focus of research is sirkukasi visitors, visitor circulation pattern will be seen in detail segingga will note a relationship between circulation pattern with grooves keramain visitors. Circulation pattern itself occurs because of the arrangement of the spaces within the shopping center consists of retail shops among other facilities along. Spaces are arranged in such sedemkian, thus indirectly shape the flow of circulation patterns, visitors. Space in the center of the magnet laying perelanjaan determining equitable circulation flow in the building. Each shopping center has a groove pattern sirkuasi different depending on the configuration of the space, because the circulation is determined by the configuration of the room. Margo City has a circulation pattern Linear Because of the configuration space of pertokoannya arranged in series based on the horizontal axis (longitudinal). Judging from the pattern of spatial arrangement of the circulation pattern liner owned by Margocity make visitors easy access to the train-destination retail stores. Magnet space on the top floor of the building Margocity is 21 or cinema theater and electronic center, for that is a magnet Baah floor space is Giant wholesale and retail stores daily necessities and ATM Center. Keywords: circulation patterns, the mall, Margocity, the spead of visitors